The Role of Knowledge Management in Achieving Organizational Ambidexterity – A Field Study on the General Directorate of Education in Jeddah Governorate – - Almehmadi, Amjad Rajaallah; Alqurashi, Suzan Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to identify the role of Knowledge Management with its dimensions (knowledge generation, knowledge storage, knowledge distribution, knowledge application) in the achievement of Organizational Ambidexterity with its two dimensions (exploitation, exploration) in the General Directorate of Education in Jeddah. The study’s problem was the question: What is the role of knowledge management in achieving organizational ambidexterity in the General Directorate of Education in Jeddah? The study has a theoretical importance as it contributes to enriching knowledge by defining the relationship between knowledge management and organizational ambidexterity, and its applied importance is the contribution of its results and recommendations to the upgrading of Directorate and making it ambidextrous through attention to knowledge management and its optimal employment, hypotheses were developed to study the impact of knowledge management dimensions in achieving organizational ambidexterity at the level of statistical significance (α≥0.05) and to find statistically significant differences between the responses of the sample members about the application of knowledge management and organizational ambidexterity due to personal and occupational variables. The descriptive analytical method was applied in order to achieve the objectives of this study. Both questionnaire and interviews were used as the tools for data collection. The study population covered all the employees of the departments of (1114) employees. A simple random sample of (286) employees was taken. Interviews were held with (29) of the Directorate employees. After processing the data statistically, several findings were reached, the most important of which are: there was a statistically significant effect for the dimensions of Knowledge Management (knowledge generation, Knowledge storage, knowledge application) in the achievement of Organizational Ambidexterity in the Directorate. The study presented several recommendations, the most important of which are: Enhancing practices contributing to knowledge generation and acquisition and establishing organizational units for the exploitation and exploration activities while defining work methods and administrative practices, training their staff and enhancing their skills.